Computer modelling of a new simple chaotic generator - Rusyn, V.; Sadli, M.; Mamat, M.; Mujiarto, .; Mada Sanjaya, W.S. (2020)
In this paper, a new circuit of a generator that realizes chaotic behavior is presented. This oscillator-circuit contains four resistors, two capacitors, one inductor, one diode, one operational amplifier and one voltage source. The proposed circuit was modeled by utilizing NI's MultiSim software environment. The system's behavior was investigated through numerical simulations, by using well-known tools of nonlinear theory, such as phase portrait, chaotic attractor and time distributions of two chaotic system-variables. This proposed circuit of chaotic generator can be used as a main part of modern systems transmitting and receiving information for masking and decryption of an information carrier.